Preoperative planning software in vertebrology: issues and outlook - Fedonnikov, Alexander S.; Kovtun, Anatoly L.; Kossovich, Leonid Y.; Kirillova, Irina V.; Kolesnikova, Anna S.; Norkin, Igor A. (Russian open medical journal, 2017)
It is established that relevance of the use of computer systems of the preoperative planning in activities of scientific and medical staff was confirmed 62.3% of the respondents. According to the survey 34.4% of respondents do not use any computer planning systems, and 21.3% of respondents could not name any specific system they are using. Problem of the lack of systematic training of specialized professionals working with specialized software products was revealed – 62.3% of respondents obtain the information about the specialized software products only in the frames of various kinds of conferences and workshops.